The role of incretin-based therapies in the management of type 2 diabetes mellitus: perspectives on the past, present and future - Juris J. Meier (Endocrinology Research Centre, 2019)
The ever-increasing burden of type 2 diabetes mellitus (T2DM) worldwide, has led to the emergence of several antidiabetes drugs with different modes of action. Incretin hormones and their effect on glucose metabolism and pathogenesis of T2DM has been a landmark discovery in the management of this increasingly prevalent metabolic disorder. Glucagon like peptide-1 (GLP-1) receptor agonists and dipeptidyl peptidase-4 (DPP-4) inhibitors are the two major classes of incretin-based therapies that regulate glucose mechanism through multiple pathways, demonstrate weight loss (GLP-1 receptor agonists) or a weight-neutral effect (DPP-4 inhibitors), and are associated with a low risk of hypoglycaemia and other adverse events. In addition, evidence reflects their possible therapeutic potential in the treatment of other clinical conditions such as obesity, cardiovascular disease and liver disorders. This review explores the availability and the impact of GLP-1 receptor agonists and DPP-4 inhibitors as potential therapeutic strategies for T2DM along with their future in the landscape of diabetes management and other clinical conditions.